Group cohesion, motor self-efficacy, and socio-emotional skills in physical education students in a region of Spain: a descriptive study - García-Guillén, María José; Castillo-Paredes, Antonio; Galán-Arroyo, Carmen; Rojo-Ramos, Jorge (Frontiers in Psychology, 2025)
IntroductionUnderstanding the impact of physical activity, mobile device use, and sociodemographic variables on students' psychosocial development is key to promoting healthier and more inclusive educational environments. This study examined how factors such as gender, age, geographic location, PA, and mobile device use influence group cohesion, motor self-efficacy, frustration tolerance, and social skills in primary and secondary school students.MethodsA cross-sectional design was used with a large sample of school-aged children and adolescents. The study assessed group cohesion, motor self-efficacy, frustration tolerance, and social skills through validated scales. Statistical analyses included t-tests, effect sizes (Hedges' g), Spearman correlations, and multiple linear regressions to examine relationships and predictive models across sociodemographic and behavioral variables.ResultsGirls scored significantly higher in assertiveness, frustration tolerance, and communication and conflict resolution skills. Rural students outperformed their urban peers across several psychosocial dimensions. Higher PA levels were associated with increased motor self-efficacy and group cohesion, particularly in boys. Excessive mobile device use correlated negatively with communication and conflict resolution skills, especially in girls. Regression analyses revealed that variables such as PA, sex, and mobile device use significantly predicted group cohesion and communication skills. Frustration tolerance and conflict resolution were notably influenced by communication skills and assertiveness, respectively.ConclusionRegular engagement in physical activity and reduced mobile device use are positively associated with students' psychosocial competencies. These findings highlight the need for targeted educational interventions that consider students' age, gender, and behavioral habits.